Determinants of destination image and their relationship with intention to visit Phuket - Madden, Ketwadee (2017)
Destination image is influenced by a number of determinants and can have a direct impact on tourists’ future behaviour. This research therefore aims to establish the determinants of destination image and its influence on tourists’ intention to visit. Due to its global popularity and large number of visitors, Phuket was selected as the study area. A survey, distributed using simple random sampling, was used to collect data from international tourists who entered Thailand through international airports. Findings based on a sample of 400 respondents showed that external motivation, internal motivation, and word-of-mouth have significant positive influence on destination image. However, perceived travel risk has a negative influence on destination image. These four variables also had an impact on intention to visit. Destination image was found to have a significant mediating influence on intention to visit. The results of this research could assist industry players by providing them with a clearer understanding of the variables that influence destination image, which could directly impact their business. Theoretically, these results enrich the literature by offering a detailed explanation of the mechanism for destination image composition, as well as formation and enhancement of existing theories, such as motivation theory of destination image formation. Future research could focus on incorporating and testing demographic and geographic influences on destination image.